Systematic Literature Review: Examining Indonesia's Educational Inequality Factors and Government Equity Policies - Zainuddin Muchtar; Chairul Omar Muchtar; Atikah Aulia Purba; Julia Sintya Sitorus; Mouces Ferdinan Siagian; Nazwa Malika Harahap; Rehia Angelica Ginting; Melly Br Bangun (International Journal of Educational Practice and Policy, 2025)
Education inequality in Indonesia remains a complex challenge, especially in remote areas and low-income communities. This study uses the Systematic Literature Review (SLR) method to identify the main factors causing education inequality, such as limited infrastructure, shortage of qualified teaching staff, socio-economic barriers and government policy implementation constraints. The findings reveal that inadequate infrastructure and a shortage of qualified teachers are prevalent in rural and underdeveloped regions, significantly limiting educational quality. Geographical disparities and socio-economic challenges further exacerbate these inequalities, creating systemic barriers to equitable access. While programs such as the Indonesia Smart Program (PIP) and School Operational Assistance (BOS) have provided partial relief, their effectiveness is often hampered by unequal resource distribution and bureaucratic inefficiencies. This study recommends a data-driven approach for more effective resource allocation, cross-sector collaboration and strengthening of education policies to create an inclusive and sustainable education system. The findings provide important insights for policymakers to overcome structural barriers and ensure equitable education for all Indonesian children.